VISUALIZATION OF CHROMOSOME-SPECIFIC DNA SEQUENCES BY FLUORESCENCE IN SITU HYBRIDIZATION OF MICRODISSECTION DNA PROBES WITH METAPHASE CHROMOSOMES - A. G. Bogomolov; K. S. Zadesenets; T. V. Karamysheva; N. L. Podkolodnyi; N. B. Rubtsov (Вавиловский журнал генетики и селекции)
Presently, suppression of repetitive DNAsequences (chromosomal in situ suppression hybridization, СISS-hybridization) is used to improve the results of fluorescence in situ hybridization (FISH). However, in some cases the suppression cannot be performed, because sufficient amounts of DNAof some species are not available. This article presents a new approach, which allows visualization of a signal from chromosome-specific DNAsequences by means of computer-assisted analysis of FISH images.